Increase Employee Motivation by Using a Democratic Leadership Style and Offering Incentives - Ismayudin Yuliyzar (International Journal of Economics and Management Research, 2023)
Democratic reform, to make employers more clean and responsible, professional to make an efficient and effective bureaucracy, and to create prime for the people. The purpose of this research is to determine the effect of democratic leadership style and incentives on motivation in the Garut Regency Regional Secretariat Office. This research is then carried out quantitatively using multiple linear regression analysis. Intention is the most powerful motivator variable. Employee motivation can be increased if the intention is carried out correctly. The t test results also show that incentives have a positive and significant influence on employee motivation at the Regional Secretariat of Garut Regency.